2019
DOI: 10.1002/jor.24532
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Temporary Epiphysiodesis With RigidTacks™ and Blount‐Staples in a Porcine Animal Model Using Magnetic Resonance Imaging

Abstract: RigidTack™ is a newly developed implant for total temporary epiphyseodesis. The implant combines the technical advantages of the traditionally used rigid Blount-staples and the newer flexible eight-plates™. Thus, the implant is rigid like the Blountstaples, which may be a biomechanical advantage in temporary epiphyseodesis, and has an easy and guided implantation technique like the eight-plate™. As in eight-plates™, supposedly only two RigidTacks™ are sufficient for temporary epiphyseodesis compared to six Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Although three staples are used in the Blount's staple technique, some authors have advocated that two nails are sufficient with U nails made of stiff material. [23][24][25] Staple configuration changes compressive forces in different axes and this can affect coronal and sagittal plane angulation. We also consider that the distance between two K-wires is different than the width of the plate, making it more effective on the lateral angle alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Although three staples are used in the Blount's staple technique, some authors have advocated that two nails are sufficient with U nails made of stiff material. [23][24][25] Staple configuration changes compressive forces in different axes and this can affect coronal and sagittal plane angulation. We also consider that the distance between two K-wires is different than the width of the plate, making it more effective on the lateral angle alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Barbed and cannulated staple prongs were employed for secure sub-periosteal bone purchase and Kirschner (K)-wire guided insertion was used in order to ensure adequate and safe placement. 25 , 27 The surgeons, who were authors of this study, performed the procedures, and the duration of surgery (incision to suture) and fluoroscopy time were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we have developed an implant for temporary ED with a reinforced crossbar and barbed, cannulated prongs for guided insertion to provide surgical simplicity, secure bone purchase, and improved clinical outcomes. Recently Hillebrand et al 25 have found a comparable efficacy between Blount staples and novel rigid staples in an animal model.…”
Section: Introductionmentioning
confidence: 96%
“…Other implants designed for temporary ED (i.e., RigidTack TM ) ( Fig. 3e) are on the market and have already been tested in animal models, but clinical data on efficacy are still missing [48]. Residual LLD after growth arrest may be treated alternatively by lengthening procedures.…”
Section: Evidence In Lldmentioning
confidence: 99%